2017
DOI: 10.1038/bmt.2017.172
|View full text |Cite
|
Sign up to set email alerts
|

Low circulating mannan-binding lectin levels correlate with increased frequency and severity of febrile episodes in myeloma patients who undergo ASCT and do not receive antibiotic prophylaxis

Abstract: Patients with multiple myeloma (MM) who undergo autologous stem cell transplantation (ASCT) are susceptible to severe infections. Low levels of circulating mannan-binding lectin (MBL) are associated with increased risk of infection. In this prospective study, we evaluated 100 patients who underwent ASCT regarding the effect of MBL on the incidence and severity of febrile episodes. Seventeen patients had MBL levels <500 ng/mL (11 received antibiotic prophylaxis and 6 did not). Although there was no statistical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
(31 reference statements)
1
3
0
Order By: Relevance
“…However, the procedure of HSCT is totally similar to the performed in a Hematology Service at present and to our knowledge, there are no extensive studies in the last years regarding the role of MBL in Allo-HSCT; in addition, our study has an important value because of a prospective cohort that included patients with myeloablative and non-myeloablative conditioning (the majority of studies on MBL and polymorphisms in patients with Allo-HSCT studied only those patients with myeloablative conditioning), this allows us to study a more heterogeneous population that is closer to the reality of the patients admitted to the Hematology Service. On the other hand, previous retrospective published studies on the role of innate immunity to infection or mortality in HSCT patients included old cohorts [14, 23], when probably viral and aspergillus prophylaxis were different to ours, with similar findings.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…However, the procedure of HSCT is totally similar to the performed in a Hematology Service at present and to our knowledge, there are no extensive studies in the last years regarding the role of MBL in Allo-HSCT; in addition, our study has an important value because of a prospective cohort that included patients with myeloablative and non-myeloablative conditioning (the majority of studies on MBL and polymorphisms in patients with Allo-HSCT studied only those patients with myeloablative conditioning), this allows us to study a more heterogeneous population that is closer to the reality of the patients admitted to the Hematology Service. On the other hand, previous retrospective published studies on the role of innate immunity to infection or mortality in HSCT patients included old cohorts [14, 23], when probably viral and aspergillus prophylaxis were different to ours, with similar findings.…”
Section: Discussionsupporting
confidence: 62%
“…However, these observations were not consistent in all study cohorts [1113]. In autologous HSCT [1417] showed conflicting results regarding the influence of MBL2 genotype and functional MBL deficiency on infection risk. In myeloablative, total body irradiation (TBI) -conditioned transplantation-, MBL2 variants have been associated with an increased risk of infection [18].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Molle et al [ 108 , 109 ] found that MBL protects MM patients treated with melphalan and autologous haematopoietic stem cells transplantation (auto-HSCT) from severe infections, accompanied by septicaemia. Eleutherakis-Papaiakovou et al [ 110 ] supported that conclusion to some extent, by showing the (relatively slight) association of low (<0.5 µg/mL) MBL, with an enhanced incidence of febrile episodes in a similar group of patients. Earlier, Kilpatrick et al [ 111 ] noted more severe infections in patients with haematological malignancies when MBL serum concentration did not exceed 0.1 µg/mL.…”
Section: Associations Of Lectin Pathway Components With Haematologmentioning
confidence: 87%